Polypyrrole/TiO2 nanotube arrays with coaxial heterogeneous structure as sulfur hosts for lithium sulfur batteries - Zhao, Yun; Zhu, Wen; Chen, George Z.; Cairns, Elton J. (Elsevier, 2016)
The lithium-sulfur cell has shown great prospects for future energy conversion and storage systems due to the high theoretical specific capacity of sulfur, 1675 mAh g−1. However, it has been hindered by rapid capacity decay and low energy efficiency. In this work, polypyrrole (PPy)/TiO2 nanotubes with coaxial heterogeneous structure as the substrate of the cathode is prepared and used to improve the electrochemical performance of sulfur electrodes. TiO2 nanotubes decorated with PPy provide a highly ordered conductive framework for Li+ ion diffusion and reaction with sulfur. This architecture also is helpful for trapping the produced polysulfides, and as a result attenuates the capacity decay. Furthermore, the heat treatment temperature used in the sulfur loading process has been confirmed to have an important impact on the overall performance of the resultant cell. The as-designed S/PPy/TiO2 nanotube cathode using an elevated heating temperature shows excellent cycling stability with a high discharge capacity of 1150 mAh g−1 and average coulombic efficiency of 96% after 100 cycles.